Mekanisme Kerja Humas dan Keprotokolan di Dinas Komunikasi, Informatika dan Persandian Kabupaten Simeulue - Selfia Anggraini; Said Fadhlain (Publikasi Indonesia, 2022)
Protocol is a series of activities related to order in the state or official events, including placement, ceremonial procedures, and procedures for respect, as a form of respect for a person based on his position in the state, government, or society. This protocol is described in Law Number 9 of 2010 concerning Place Arrangements, Honorary Procedures, and Government Regulation Number 62 of 1990 concerning Provisions for Placement Procedures, Honorary Procedures, and Respect Procedures. The purpose of this research is to know the working mechanism of Public Relations and Protocol of the Office of Communication, Information and Encryption of Simeulue Regency and the obstacles faced when implementing the work mechanism. The method used in this study is a qualitative descriptive method. This research was carried out during public relations and protocol training which was held directly at the Office of Communication, Information and Encryption, Simeulue Regency. The theory used is organizational communication theory and public communication theory. The results of this study explain that in order to carry out the work mechanism of Public Relations and Protocol in Simeulue Regency, it is necessary to prepare protocol officers who play a dominant role in protocol activities which basically add color and image to the success of organizing state events or ceremonies or as well as influencing the image of the national government, the state. sections, centers and regions.